The Study of Dragonfly (Odonata) Diversity as Bioindicator of Water Quality in Science Techno Park Spring-Beleknehe Village - Chatarina Gradict Semiun; Yulita Iryani Mamulak; Emilianus Pani; Stefanus Stanis (Jurnal Biologi Tropis, 2023)
Dragonflies are bioindicator insects for the quality of the aquatic environment, especially springs. This study aims to determine the types of dragonflies that live in the Science Techno Park (STP) spring, Beleknehe village, Nekemese sub-district, Kupang District. STP is owned by Widya Mandiri Catholic University. This research was conducted in September 2022. Data collection consisted of dragonfly samples and abiotic factors. Dragonfly samples were obtained using insect nets and hand sorting, while abiotic factor measurements included physical (TDS, DHL) and chemical (hardness, iron, sulfate, Mn, NO3, NO2) parameters. The results of the study revealed that there were four types of dragonflies namely Neurothemis stigmatizans, Coenagrion lunulatum, Megalagrion sp., and Orthetrum pruinosum. The four dragonflies found showed that the quality of the Science Techno Park spring was still in good condition.